The Effect of Time-limited Products on Consumers’ Buying Decision: An Empirical Research in Taiwan - Feng, Y.T. (2017)
Launching time-limited goods are widely used by marketers to attract consumers and extending the market shares in these decades. Time-limited products have proved with a positive effect on consumers’ buying purchase intention in several studies. However, there are few current findings of the impact of time-limited products on purchase intention, owing to the lack of clarifying the determinants factors of time-limited products. For instance, attitude towards time-limited goods, the attractiveness of time-limited products and the price which are the primary variable of influencing the intention to attract consumers. Therefore, it is necessary to study these three factors to estimate its effects on consumers’ buying intention.